Portable Nanocomposite System for Wound Healing in Space - Chiara Zagni; Andrea Scamporrino; Paolo Maria Riccobene; Giuseppe Floresta; Vincenzo Patamia; Antonio Rescifina; Sabrina Carroccio (2023)
It is well known that skin wound healing could be severely impaired in space. In particular, the skin is the tissue at risk of injury, especially during human-crewed space missions. Here, we propose a hybrid system based on the biocompatible poly 2-hydroxyethyl methacrylate (pHEMA) to actively support a nanocontainer filled with the drug. Specifically, during the cryo-polymerization of HEMA, halloysite nanotubes (HNTs) embedded with thymol (Thy) were added as a component. Thy is a natural pharmaceutical ingredient used to confer wound healing properties to the material, whereas HNTs were used to entrap the Thy into the lumen to ensure a sustained release of the drug. The as-obtained material was characterized by chemical–physical methods, and tests were performed to assess its ability for a prolonged drug release. The results showed that the adopted synthetic procedure allows the formation of a super absorbent system with good swelling ability that can contain up to 5.5 mg of Thy in about 90 mg of dried sponge. Releasing tests demonstrated the excellent material’s ability to perform a slow controlled delivery of 62% of charged Thy within a week. As humans venture deeper into space, with more extended missions, limited medical capabilities, and a higher risk of skin wounds, the proposed device would be a versatile miniaturized device for skin repair in space.